Using Simulation for Development of The Systems of Automobile Gas Diesel Engine and its Operation Control - G. Shatrov, Mikhail; V. Sinyavski, Vladimir; Yu. Dunin, Andrey; G. Shishlov, Ivan; V. Vakulenko, Andrey; L. Yakovenko, Andrey (International Journal of Engineering and Technology, 2018)
The work was aimed at the development of gas supply, diesel fuel supply and electronic control systems for automobile gas diesel engines. Different ways of diesel engine conversion to operate on natural gas were analyzed. Gas diesel process with minimized ignition portion of diesel fuel injected by the CR system was selected. Electronic engine control and modular gas feed systems which can be used on high- and middle-speed gas diesel engines were developed. Diesel CR fuel supply system was developed in cooperation with the industrial partner. Simulation was used to obtain basic parameters and control methods of these systems. The base diesel engine was converted into gas diesel engine using the systems developed. Bench tests of the gas diesel engine demonstrated a high share of diesel fuel substitution with gas, high fuel efficiency and large decrease of NOÑ… and Ð¡Ðž2 emissions.Â